Joint Opportunistic Power Scheduling and End-to-End Rate Control for Wireless Ad Hoc Networks - Lee, Jang-Won; Mazumdar, Ravi R.; Shroff, Ness B. (IEEE transactions on vehicular technology, 2007)
It is known that opportunistic scheduling that accounts for channel variations due to mobility and fading can give substantial improvement over nonopportunistic schemes. However, most work on this subject has focused on single-hop cellular types of architectures. The situation is quite different in ad hoc networks due to the inherent multihop nature of transmissions. In this paper, we present a joint opportunistic power scheduling and e nd-to-end rate control scheme for wireless ad hoc networks. We model the time-varying wireless channel as a stochastic process and formulate a stochastic optimization problem, which aims at maximizing system efficiency by controlling the power allocation of each link and the data rate of each user in the system. The joint power scheduling and rate control algorithm is obtained by using stochastic duality and implemented via stochastic subgradient techniques. We illustrate the efficacy of our approach via numerical examples.